2013
DOI: 10.1590/s2237-60892013000100004
|View full text |Cite
|
Sign up to set email alerts
|

Treating refractory obsessive-compulsive disorder: what to do when conventional treatment fails?

Abstract: Tratando o transtorno obsessivo-compulsivo refratário: o que fazer quando tratamentos convencionais falham? Treating refractory obsessive-compulsive disorder:what to do when conventional treatment fails? AbstractObsessive-compulsive disorder (OCD) is a chronic and impairing condition. A very small percentage of patients become asymptomatic after treatment. The purpose of this paper was to review the alternative therapies available for OCD when conventional treatment fails. Data were extracted from controlled c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…Franz et al (29) in their study searched for the most efficient therapeutic approach for OCD, refractory cases in particular, and found that the use of clonidine in combination with SSRIs for two weeks could alleviate OCD symptoms; however, these effects remained uncertain and limited to some cases, necessitating further evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Franz et al (29) in their study searched for the most efficient therapeutic approach for OCD, refractory cases in particular, and found that the use of clonidine in combination with SSRIs for two weeks could alleviate OCD symptoms; however, these effects remained uncertain and limited to some cases, necessitating further evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…The most common and effective evidence-based treatment for OCD includes selective serotonin reuptake inhibitors (SSRIs) and cognitive behavioral therapy with exposure and response prevention (Abramowitz & Arch, 2014;Franz et al, 2013;Pauls et al, 2014). Limitations in the development and promotion of treatment for the minority population and the lack of professional cultural competence emphasizes the need for research that includes ethnic considerations (Williams et al, 2010;Zane et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the growing trend of aripiprazole seems that soon this antipsychotic agent replaced the use of quetiapine in the treatment of refractory OCD. As the treatment of refractory OCD generally requires high doses of SSRIs, this higher dose increases the side effects, especially loss of sexual drive [133].…”
Section: Discussionmentioning
confidence: 99%